The implementation of choral reading method in improving student’s reading fluency - Ayuba, Hasan; Kadir, Lince (English Education Department, 2022)
This study aims to improve students' Students Reading Fluency through Choral Reading Method at the Seventh Grade Students of SMP N. 1 Botupingge. This research is a Classroom Action Research (PTK). The subjects of this study are the students of grade VII SMP N. 1 Botupingge who numbered 22 students. This study consists of two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Data collection techniques used in this study is test observation, and documentation. The research instruments used include the observation sheet, the test of reading fluency (accuracy, Rate, and Prosody) and documentation. The collected data were analyzed using qualitative descriptive analysis technique and supported by quantitative data. The results of this study indicate that the implementation of choral reading can improve students’ reading fluency in students of class VII SMP N. 1 Botupingge both in terms of process and product. The improved processes can be seen in student activities in the learning process. This is indicated by the increase of students in attention to learning, enthusiastic liveliness, and atmosphere of learning in the classroom more conducive. Improving process quality has a positive impact on product quality improvement. This is seen in the test results of reading fluency starting from cycle 1 up to cycle 2. Based on this result, it can be concluded that choral reading method can improve students’ reading fluency at seventh grade of SMP N. 1 Botupingge.